Analisis Bibliometrik Peran Orang Tua terhadap Perkembangan Bahasa Anak Usia Dini - Erma Noviana Pratiwi; Purwandari, Eny (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Language development in early childhood is a crucial aspect influenced by the social environment, especially the role of parents as the child's closest figures. Parents play a strategic role in providing stimuli that accelerate children's language acquisition through communication, interaction, and modeling. Objectives: This article aims to examine the role of parents in the language development of early childhood through a theoretical review using a bibliometric approach. Methods: The method employed involves bibliometric analysis supported by Publish or Perish software for metadata collection and VOSviewer for literature mapping. Results: show that the keywords "early childhood," "language development," and "parental role" dominate the relevant literature, with high frequency and strong relevance scores. Visual mapping also reveals that the connection between parental roles and children's language development is a central theme with clear thematic clustering. Conclusion: In conclusion, parental involvement is crucial in supporting early childhood language development, in line with Vygotsky's perspective on the importance of social interaction and scaffolding in children's language acquisition.  Keywords : Parental Role, Language Development, Early Childhood, Vygotsky, Bibliometric